Effets de sens dérivés de la qualification adjectivale - Christopher Desurmont (Anglophonia)
This paper bears upon three classes of adjectives: qualifying (speaker oriented), descriptive (intersective/non intersective), and (role-based) participles. The aim here is to show that a full interpretation of adjectival qualification needs to take into account semantic components over and above the “surface meaning” (or denotation): the positional properties of the attributive adjective; representation in terms of sets and subsets; interpretation of the qualifying adjective (here: the adjective nice) filtered through a positional property and the relevant components of its environment; interpretation of participle adjectives (slanting rain, enclosed garden) in terms of argument structure and semantic roles.